Analisis Prosedur Penerimaan Kas Pada PT. POS (Persero) Pematangsiantar - Asmawati Halilah Damanik; EVE IDA MALAU; Richard Berlien (Jurnal Akuntansi Dan Manajemen Indonesia (JAMIN), 2021)
The purpose of this study was to determine the analysis of cash receipts procedures at PT. Indonesian post. Cash receipts that occur at PT. Pos Indonesia come from many types of transactions. The writing focuses on cash receipts that come from sending postal packages, because it is a transaction that still often occurs even though there are other goods delivery service companies. The recording and bookkeeping system carried out at PT. Pos Indonesia is in accordance with the procedures established by the head office and the bookkeeping is carried out very consistently and thoroughly. The analysis technique used is a qualitative approach. With this cash receipt procedure, it is hoped that it can assist financial activities in processing cash flow reports and presenting them in the form of reports quickly, easily and accurately. Thus, the existence of a cash flow reporting system that is designed can be implemented properly and helps to minimize the problems that are being faced by PT. Pos (PERSERO). It is expected that the cash receipts process will run effectively and efficiently.